Pengaruh Kepemimpinan dan Motivasi terhadap Kinerja Guru dan Pegawai pada Sekolah Menengah Pertama Kemala Bhayangkari 01 Makassar - Sanusi, M. Dahkri; Arief, Syariuddin (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This research aims to find out how much influence leadership has on the performance of teachers and employees and how much influence motivation has on the performance of teachers and employees at Kemala Bhayangkari 01 Makassar Junior High School. The type of research used is quantitative analysis, namely the author describes the results of observations and analyzes data obtained in the field using multiple linear regression. Based on the research results, it shows that the performance of employees at Kemala Bhayankari 01 Makassar Junior High School is generally still in the medium category. The existence of employee performance in the medium category is caused by the leadership and employee motivation variables at Kemala Bhayankari 01 Makassar Junior High School which are still in the medium category and the benefits of internal and external motivation have not been optimal for the entire employee performance process, leadership makes a significant contribution in a positive direction. This means that the leadership variable influences employee performance improvement. The increase in employee performance caused by leadership variables was 62.3% while the remaining 37.7% was explained by factors other than leadership variables. Thus, this shows that leadership variables are important to pay attention to in explaining employee performance.